Estrategias de marketing político digital implementadas en la campaña de Guillermo Lasso para las elecciones presidenciales 2021. - Ramon Ordoñez, Bladimir Alexander (My University, 2020)
The objective of this research was focused on analyzing the digital political platforms and establishing the strategic roles of candidate Guillermo Lasso, through an exploratory study with a qualitative approach, based on the MERCO and AIDA technique, for the strategic identification of digital political marketing implemented in the 2021 presidential elections; Thus, the investment applied in digital advertising is $ 39,000 per month, especially on Facebook, a platform which represents 59% of its total followers, followed by Twitter with 35% and Instagram 6%; Indeed, communication efforts based on the AIDA technique focused on the promise called "The Government of Change" as a message that generates attention and interest, in addition, the communication of the government plan with positive changes in the economic axes, education, health and safety to provoke the desire to believe in him and his proposal, thus having greater supporters who contribute to the action of voting in favor of his political candidacy.
El objetivo de esta investigación, se centró en analizar las plataformas políticas digitales y establecimiento de roles estratégicos del candidato Guillermo Lasso, mediante el estudio de carácter exploratorio con enfoque cualitativo, basado en la técnica MERCO y AIDA, para la identificación estratégica de marketing político digital implementadas en las elecciones presidenciales 2021; tal manera, la inversión aplicada en publicidad digital es de $39.000 mensuales, especialmente en Facebook, plataforma la cual representa el 59% del total de sus seguidores, seguidamente Twitter con 35% e Instagram 6%; en efecto, los esfuerzos en comunicación basados en la técnica AIDA se centraron en la promesa denominada “ El Gobierno del cambio” como mensaje generador de atención e interés, además, la comunicación del plan de gobierno con cambios positivos en los ejes económicos, educación, salud y seguridad para provocar el deseo de creer en él y su propuesta, teniendo así mayores adeptos que contribuyan a la acción de votar a favor de su candidatura política.
Keywords: MARKETING POLÍTICO; MARKETING DIGITAL; COMUNICACIÓN POLÍTICA; SOCIAL MEDIA